Shade alters the growth and architecture of tropical grasses by reducing root biomass. (7th March 2021) - Solofondranohatra, Cédrique L.; Vorontsova, Maria S.; Dewhirst, Rebecca A.; Belcher, Claire M.; Cable, Stuart; Jeannoda, Vololoniaina; Lehmann, Caroline E.R.
Abstract: Tropical grassy biomes have variable tree cover and are often characterized by a flammable grassy ground layer where the dominating grass species have strategies to persist and proliferate with frequent fire. However, there is limited understanding of how grass growth and flammability traits respond to light availability. We experimentally grew 14 grass species characteristic of the Malagasy Central Highlands for one year with four treatments of light exclusion ranging from 0 – 60%. Eight plant functional traits and four leaf flammability traits were measured: plant height, bulk density, aboveground biomass, belowground biomass, ratio of root to shoot biomass, specific leaf area, leaf length, leaf width, leaf heat release capacity, temperature of maximum decomposition, total heat release and peak heat release rate. Belowground biomass, the ratio of root to shoot biomass, and bulk density were all negatively affected by decreasing light availability. Surprisingly, aboveground biomass showed no significant change with changing light availability, although there was a trend toward shorter plants in low light. At a leaf level, declining light availability increased specific leaf area, leaf length, and leaf width. In terms of leaf flammability, of the four traits measured, unexpectedly, only leaf total heat release was significantly positively related to declining light availability. These results suggest field alterations in grass flammability may be primarily related to plant architecture and microclimates. The shifts in allometry and substantial reduction in belowground biomass suggest that grasses would be rapidly lost from shaded environments with a diminished competitive capacity to resprout. Abstract : How the growth and architecture of tropical grasses respond to changes in light availability and tree cover is little studied. We experimentally grew 14 grass species characteristic of the Malagasy Central Highlands for one year with four treatments of light exclusion ranging from 0 to 60%. The shifts observed in allometry and substantial reduction in belowground biomass suggest that grasses would be rapidly lost from shaded environments with a diminished competitive capacity to resprout.